2019
DOI: 10.3390/cells8080865
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Attenuates Doxorubicin-Induced Cardiac Dysfunction and Inhibits Endothelial-to-Mesenchymal Transition in Mice

Abstract: Doxorubicin (Dox) is an effective anti-neoplasm drug, but its cardiac toxicity limits its clinical use. Endothelial-to-mesenchymal transition (EndMT) has been found to be involved in the process of heart failure. It is unclear whether EndMT contributes to Dox-induced cardiomyopathy (DoIC). Calcitriol, an active form Vitamin D3, blocks the growth of cancer cells by inhibiting the Smad pathway. To investigate the effect of calcitriol via inhibiting EndMT in DoIC, C57BL/6 mice and endothelial-specific labeled mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 63 publications
2
19
1
Order By: Relevance
“…A recent study showed that the classic TGF-β/smads pathway was involved in DOX-induced EndMT of CMECs [ 34 ], which is inconsistent with our results. In their in vitro experiments, the phenotype of EndMT was not induced by DOX stimulation, but directly by TGF-β treatment, which was not rigorous.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study showed that the classic TGF-β/smads pathway was involved in DOX-induced EndMT of CMECs [ 34 ], which is inconsistent with our results. In their in vitro experiments, the phenotype of EndMT was not induced by DOX stimulation, but directly by TGF-β treatment, which was not rigorous.…”
Section: Discussioncontrasting
confidence: 99%
“…Calcitriol, an active form of vitamin D3 that inhibits the growth of cancer cells, has been shown to attenuate Doxinduced myocardial fibrosis and fibrotic proteins, and improve diastolic function by reducing TGF-β-Smad2mediated EndMT and fibroblast-to-myofibroblast transition. The hearts of mice with EC-specific GFP expression showed increased levels of vimentin + GFP + ECs (indicative of EndMT), whereas calcitriol treatment attenuated these effects 79 . Administration of arsenic trioxide induced cardiac fibrosis in rats.…”
Section: Cardiotoxicity Of Anticancer Drugsmentioning
confidence: 99%
“…A landmark study published in 2007 confirmed that EndMT is involved in cardiac fibrosis of the adult heart ( Zeisberg et al, 2007 ). Many studies demonstrated that the inhibition of EndMT might be a useful strategy in the therapy of cardiac fibrosis ( Song et al, 2019 ; Tsai et al, 2019 ). In this study, we demonstrated the potential regulation of KLX on EndMT in TAC mice.…”
Section: Discussionmentioning
confidence: 99%